A child with Myhre syndrome presenting with corectopia and tetralogy of Fallot. Issue 2 (12th December 2017) - Alagia, Marianna; Cappuccio, Gerarda; Pinelli, Michele; Torella, Annalaura; Brunetti‐Pierri, Raffaella; Simonelli, Francesca; Limongelli, Giuseppe; Oppido, Guido; Nigro, Vincenzo; Brunetti‐Pierri, Nicola; ,
Abstract : Myhre syndrome is a rare autosomal dominant disorder caused by a narrow spectrum of missense mutations in the SMAD4 gene. Typical features of this disorder are distinctive facial appearance, deafness, intellectual disability, cardiovascular abnormalities, short stature, short hands and feet, compact build, joint stiffness, and skeletal anomalies. The clinical features generally appear during childhood and become more evident in older patients. Therefore, the diagnosis of this syndrome in the first years of life is challenging. We report a 2‐year‐old girl diagnosed with Myhre syndrome by whole exome sequencing (WES) that revealed the recurrent p.Ile500Val mutation in the SMAD4 gene. Our patient presented with growth deficiency, dysmorphic features, tetralogy of Fallot, and corectopia (also known as ectopia pupillae ). The girl we described is the youngest patient with Myhre syndrome. Moreover, corectopia and tetralogy of Fallot have not been previously reported in this disorder.